Comparison of orthogonal versus parallel double plating technique in patients type C distal humeral fractures: a randomised control trial - Sarode, Rohan; Mitra, Sajal R.; Sah, Saurabh; Sakharkar, Nilesh S.; Adewar, Aniket (International Journal of Research in Orthopaedics, 2023)
Background: Distal humerus fracture accounts approximately 2%-6% of all fractures and 30% of all elbow fractures, intra articular distal humerus fracture are rare accounting 0.5% of all fractures. These fractures had bimodal distribution, with respect to age and gender, with peaks of incidence in males aged 12 to 19 years and females aged 80 years and over. Methods: Patients were randomly divided into two groups, one undergoing perpendicular plating with 17 patients and the other parallel plating with 17 patients. Patients were followed up minimally for 12 months. Results: We observed that time of union for parallel plating method was 12.82 weeks and 12 weeks in orthogonal plating. In our study functional outcome based upon Mayo elbow performance score, in group 1 (Parallel plating) was excellent in 7 patients (41.17%), good in 6 patients (35.29%), fair in 4 patients (23.52%). Conclusions: In terms of arc of motion and stability a good to excellent functional outcome was achieved in >85% of the study group. In cases of osteoporotic and comminuted bones, a rigid construct must be achieved.